Pemaafan pada istri dewasa muda yang suaminya pernah berselingkuh - Steven, Yulius; Sukmaningrum, Evi (Konsorsium Psikologi Ilmiah Nusantara, 2018)
This study examined forgiveness process and its associated affecting factors among young adult wives as they overcome their spouse’s infidelity. The present study used qualitative study with in-depth interviews to explore those variables and also employed two questionnaires – NEO PI-R and TRIM-18 – to measure the personality factor and the forgiveness motivation. To recruit participants, convenience sampling technique was employed. This study showed that all three participants have not yet reached the final stage of forgiveness. Rumination was found in all participants as the barrier aspect that affects the process. Other factors that promote forgiveness process were reasons of forgiving, sincere apology from husband, relationship quality, and high motivation of benevolence. Furthermore, cultural and religious factors play a major role in forgiving process.